Kreativitas Belajar - Markus Oci (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
Creativity is the ability to create something new from data, information, or elements thatalready exist. Learning is a process that brings wholistic change in behavior and thinking,as a result of a person’s experience interacting with the environment. Creativity is theability to learn to solve problems and create new things. Learning creativity can bedeveloped through various means, media, or stimulus introduced into the learningenvironment. Cultivitaing creativity requires a wide space, supporting facilities, andadequate infrastructures for developingthese abilities.